Peningkatan Social Media Marketing Melalui Pelatihan Fotografi Produk Pada UMKM Berbasis Ekonomi Kreatif Melalui Produk - Ula Farhah Nailah; Dewi Deniaty Sholihah (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
MSMEs are the initial pillars of economic development in Indonesia, many efforts have been made by the government. Creative Economy is a government program concept aimed at strengthening MSMEs in Indonesia. Product branding is part of innovation and creativity to add value to a product. The purpose of creating this magazine is to build a Cendol Suji MSME product brand with a product branding strategy through product photos. This activity uses observation, interviews and technology. Activities to empower MSMEs with assistance in product photography ranging from product photography to retouching. This will provide a new perspective for MSME actors to brand their products so that they can compete in the open market. Through this collection of photos, MSMEs can promote their products through e-commerce, such as online shops, shopee, tokopedia, grab, etc.